ChemInform Abstract: Aerobic Dehydrogenative Heck Reactions of Heterocycles with Styrenes: A Negative Effect of Metallic Co‐Oxidants. Issue 24 (23rd May 2013) - Vasseur, Alexandre; Harakat, Dominique; Muzart, Jacques; Le Bras, Jean
Abstract Aerobic dehydrogenative Heck reactions of heterocycles with styrene derivatives are shown to be more efficient in the absence of metallic co‐oxidants.